IMPLEMENTASI VISI KOTA PEKANBARU : PERWUJUDAN KEAMANAN DAN KETERTIBAN UMUM KOTA METROPOLITAN YANG MADANI TAHUN 2012-2015 - Friski Febriyan; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The background of this study to the vision set by the Government between Pekanbaru years 2012-2017 that seeks to realize the Pekanbaru city as a metropolis civil. The study was conducted to analyze the implementation of Pekanbaru City Government conducted concerning security and public order in an effort to achieve the vision of Pekanbaru city, especially to the problems of society's ills and identification obstacles that are found in the implementation process. Pekanbaru City Government has outlined a vision coherently start of a mission that supports the realization of the vision, then the goals, objectives, strategies, policies and institutions that have been entrusted the task of safety issues, including the Civil Service Police Unit and the National Unity and Political Pekanbaru, then the police also have a fundamental duty safety issues.This type of research is descriptive qualitative study aimed to describe the real state of the field systematically and accurately related facts and research analysis unit, as well as field observations based on data (information) in particular. Methods of data collection is by interview, documentation and observation.The results of this study describes the implementation of the implementation of the community to address issues of disease based on the goals that have been set from the beginning. Development of community protection efforts to maintain and preserve security, order, unity, and the unity and harmony of society. In the implementation of each institution performing the task, although in the implementation find obstacles, the task can still be accomplished either in a raid, secure in-prone areas by municipal police, socialization activities conducted by Unity, and also operations that support community safety conducted by Police. In practice, each institution mutually coordinated with one another in order to ease their task by working together.Keywords: Metropolitan City Madani, Policy Implementation, Disease Society